Middle School Students' Mathematical Representational Ability: A Case Study of the Development of Students' Cognitive Ability through the Realistic Mathematics Education Approach - Intan Kemala Sari; Ahmad Nasriadi; Yuli Amalia; Musfiya Musfiya; Farida Agus Setiawati (Institut Pendidikan Indonesia Garut, 2023)
Kemampuan representasi matematis sangat penting untuk dimiliki dan dikembangkan. Penelitian ini bertujuan untuk menganalisis kemampuan representasi matematis siswa, serta bentuk representasi matematis yang muncul. Penelitian ini menggunakan studi kasus terhadap empat siswa SMP Kelas VII dengan kemampuan sedang, yang dilaksanakan dalam pembelajaran Mengenal Bentuk Aljabar. Penelitian dilaksanakan pada semester ganjil pada tahun ajaran 2022/2023 sebanyak tiga kali pertemuan. Adapun teknik pengumpulan data yang dilakukan yaitu angket, wawancara, dan lembar analisis pemecahan masalah. Hasil penelitian menunjukkan bahwa siswa kelas VII merupakan siswa tahap abstraksi awal sehingga kemampuan representasi matematis belum banyak muncul dan berkembang dengan baik. Adapun bentuk representasi yang muncul yaitu representasi simbolik dengan tipe rendah dimana masih terdapat Gap antara berpikir konkrit dengan kemampuan abstraksi awal. Beberapa hal yang mempengaruhi munculnya kemampuan representasi adalah motivasi yang tinggi dalam memecahkan masalah, metode belajar yang disajikan, dan kemampuan siswa dalam belajar matematika.Mathematical representation ability is very important to have and develop. This study aims to analyze students' mathematical representation abilities, as well as the forms of mathematical representations that appear. This study used case studies of four Grade VII junior high school students with moderate abilities, which were carried out in Recognizing Algebraic Shapes. The research was carried out in the odd semester of the 2022/2023 academic year in three meetings. The data collection techniques used are questionnaires, interviews, and problem solving analysis sheets. The results showed that class VII students were students at the early abstraction stage, so their mathematical representation abilities had not emerged and developed well. The form of representation that appears is symbolic representation with a low type where there is still a gap between concrete thinking and initial abstraction abilities. Some of the things that influence the emergence of representational abilities are high motivation in solving problems, the learning methods presented, and students' abilities in learning mathematics.